FULL-TIME EDUCATION: CURRICULAR FLEXIBILIZATION AND YOUTH PROTAGONISM - Silva Ramos, Daniele (Revista Gênero e Interdisciplinaridade, 2023)
Full-Time Comprehensive Education is an educational process aimed at the development of the student in its entirety, in its cognitive, political-social, ethical-cultural or socio-emotional aspects. This study adopts a qualitative, descriptive approach that uses theoretical contributions to investigate the challenges in the effectiveness of this extension of the student journey, taking as an essential point not only the focus on extending time, but rather a differentiated school organization, with a curriculum more diverse that allows immersion in studies and a variety of development opportunities. It proposes reflections on the impacts of these actions on the formation of youth protagonism. The results reaffirm that the Full Time Integral School is a privileged space for young people to start acting actively and decisively in their learning and life journey.